Profil Pasien Uveitis di Plokilinik Mata RSUP Dr. M. Djamil Padang Pada Tahun 2020-2022 - Helery, Muhammad Arsyan; Vitresia, Havriza; Ariani, Novita; Hidayat, Muhammad; Semiarty, Rima; Arfiani Rusjdi, Dina (Jurnal Ilmu Kesehatan Indonesia, 2025)
Uveitis is an inflammation of the middle layer of the eye, the uvea, which consists of the iris, ciliary body and choroid. Uveitis is one of the causes of ocular morbidity. Common symptoms of uveitis include red eye, eye pain and blurred vision. Patients with uveitis can experience decreased vision to blindness. Research on uveitis in Indonesia is still limited. This study aims to determine the profile of uveitis patients at the ophtalmology departement of RSUP Dr. M. Djamil Padang. This study used a descriptive research design with a retrospective approach which was carried out by observing data from the medical records of uveitis patients at the ophtalmology departement and the medical records section of RSUP DR. M. Djamil Padang period 2020-2022. The study used a total sampling technique. Patient data were analyzed univariately and data presentation in the form of frequency distribution tables. In this study, a total of 50 samples were obtained. The results of this study found out that uveitis patients mostly female (52%) and the majority in the age range 20-60 years (90%). The most common types of uveitis based on anatomical location are panuveitis (56%) and unilateral lateralization (62%). The main etiology of uveitis was infection (42%). Most of the uveitis patients had clinical manifestation of blurred vision (72%) and red eye (72%). More than half uveitis patients visus was <3/60, categorized as blindness (52%).